Adsorption of heavy metals solution on commercial activated carbon adsorbent : batch studies - Mohd Nazri Shamsudin (Penerbit Universiti Malaysia Perlis, 2011)
The ability of commercial activated carbon to adsorb Pb2+ from aqueous solution has been investigated through batch experiments. The adsorption of lead onto commercial activated carbon has been found to depend on adsorbent dose, initial concentration and contact time. The experiments were carried out at natural solution pH. Equilibrium data fitted well with the Langmuir model and Freundlich model with a maximum adsorption capacity of 23.81 mg of Pb/g of commercial activated carbon. The experiments showed that the highest removal rate was 92.42% for Pb2+ under optimal conditions. The sorption of Pb2+ on commercial activated carbon was rapid during the first 30 min and the equilibrium attained within 60 min. The kinetic processes of Pb2+ adsorption on commercial activated carbon were described by applying pseudo-first-order and pseudo-second-order kinetic models. The kinetic data for the adsorption process obeyed a pseudo-second-order kinetic model, suggesting that the adsorption process is chemisorption. The commercial activated carbon investigated in this study showed good potential for the removal of Pb2+ from aqueous solution.